Knowledge Intensive Agriculture: The New Disruptor in World Food? - Teng, Paul (2017)
New digital media are fast becoming available to convey new technology and new knowledge to farmers. Agricultural technology (“agtech”) and new financing modalities (“fintech”) have great potential to meet the needs for increasing agricultural production globally. Knowledge intensive agriculture (KIA) is increasingly becoming the next big disruptive innovation.